Pelatihan Pendidikan Karakter Disiplin Melalui Kegiatan Ekstrakurikuler Pramuka di SD Islam Raudhatul Jannah - Aprilianti , Kurnia; Fitri, Lailatul; Salsabilla , Putri; Marwan, Syaiful (PASAI : Jurnal Pengabdian kepada Masyarakat, 2023)
This research was motivated by the low disciplinary character of students in the school environment. This research focuses on how disciplined character can be embedded in scouts who raise in extracurricular scout activities at Raudhatul Jannah Payakumbuh Islamic Elementary School. The aim of this research is to describe the coaches' efforts in forming a disciplined character in students through scout activities at Raudhatul Jannah Payakumbuh Islamic Elementary School. This research was conducted at Raudhatul Janah Payakumbuh Islamic Elementary School involving 20 students who participated in scout raising activities and coaching. This type of research is qualitative research, using three data collection techniques, namely, interviews, observation and documentation. From the results of the observations carried out, it shows that scout extracurriculars can form a disciplined character in students. The formation of this disciplined character can be formed due to the efforts made by the coach by applying punishment methods and giving appreciation to students on PPB and pioneering activity material.